Methodology of residual resource assessment in the metallic structures of lifting machines - Starykov, Maksym (Transport, 2013)
One of the key problems of particular companies that operate cargo lifting machines in Ukraine (previous affiliation of author – Department of Handling Machinery and Mechanization of Reloading Work, Odessa National Maritime University, Ukraine) as well as other post-Soviet countries is that the guaranteed-by-manufacturer period of their safe exploitation has ended. Further use should be subjected to qualified inspection of the metal construction and mechanism. This article focuses on the metal constructions as they are the basis of all cargo lifting machines. Up to now, there has been no common way to determine the degradation of metal constructions and predict their residual resource. The author suggests a methodology for resolving this problem.First Published Online: 11 Oct 2013